PELATIHAN PEER COUNSELING PADA REMAJA DI PANTI SOSIAL ASUHAN ANAK (PSAA) TUNAS BANGSA PATI - Edris Zamroni; Masturi Masturi (Bagimu Negeri, 2017)
Peer counseling training activities as a way to address the lack of human resources. Peer counseling is a way for students (teens) to learn how to pay attention and to help other children, and to apply them in everyday life. The aim is to produce a peer counselor to help treat psychological problems of orphans by utilizing peer counselor. This activity was conducted in 10 times the activity began identifying candidates for peer counselors service up on basic skills training for the implementation of counseling their peers. The activities take place from December 12, 2016 - February 22, 2017 held every Wednesdays from 15.00 pm. The result obtained 15 peer counselors to service to peers.